Gleditsia species: An ethnomedical, phytochemical and pharmacological review. (3rd February 2016) - Zhang, Jian-Ping; Tian, Xin-Hui; Yang, Yong-Xun; Liu, Qing-Xin; Wang, Qun; Chen, Li-Ping; Li, Hui-Liang; Zhang, Wei-Dong
Abstract: Ethnopharmacological relevance: The plants in the genus Gleditsia, mainly distributed in central and Southeast Asia and North and South America, have been used as local and traditional medicines in many regions, especially in China, for the treatment of measles, indigestion, whooping, smallpox, arthrolithiasis, constipation, diarrhea, hematochezia, dysentery, carbuncle, etc. This present paper systemically reviews the miscellaneous information surrounding its traditional use, phytochemistry and pharmacology to provide opportunities and recommendations for the future research. Materials and methods: The scientific literatures were systematically searched from scientific databases (PubMed, Scopus, Elsevier, SpringerLink, SciFinder, Google Scholar and others). In addition, the ethnopharmacological information on this genus was mainly acquired from Chinese and Korean herbal classics, and library catalogs. Results: More than 60 compounds including triterpenes, sterols, flavonoids, alkaloids, phenolics and their derivatives were isolated from Gleditsia japonica Miq., Gleditsia sinensis Lam., Gleditsia caspica Desf. and Gleditsia triacanthos L. Among these compounds, triterpenoid saponins were the main constituents of Gleditsia species. Moreover, the crude extracts and purified molecules were tested, revealing diverse biological activities such as anti-tumor, anti-inflammatory, anti-allergic, anti-hyperlipidemic, analgesic, antimutagenic, antioxidant, anti-HIV, antibacterial, antifungal activities, etc. Among these biological studies, the possible mechanisms of antitumor action are stressed in this review, and these include causing cytotoxicity to cancer cells, inhibition of proliferation of cancer cells by affecting their growth, regeneration and apoptosis, inhibition of basic fibroblast growth factor (bFGF) and nitric oxide (NO), modulation of the oncogenic expression and telomerase activity results, inhibition of the expression of pro-angiogenic proteins, as well as down-regulation of intra/extracellular proangiogenic modulators, etc. Conclusions: On the basis of preliminary research on Gleditsia genus it could be stated that saponins investigations may be more promising in future. Although 32 compounds of 67 identified compounds were saponins, modern pharmacological research on saponins were not a priority in Gleditsia species. Therefore, more bioactive experiments and in-depth mechanisms of action are required for elucidating their roles in physiological systems. Moreover, the present review also highlights that analgesic, anti-tumor and anti-HIV activities should have priority in saponins research. Additionally, it is imperative to explore more structure–activity relationships and possible synergistic actions of triterpenoid saponins for revaluating their pharmacological activities. Graphical abstract: